2003
DOI: 10.1046/j.1365-2850.2003.00601.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of caregiving: listening to the voice of informal caregivers

Abstract: Long-term care of the elderly and the disabled rests on a vast network of informal caregivers. This qualitative study examined the effects of caregiving on the health and wellbeing of a small, non-representative sample of urban women caregivers. These 11 informants participated in two interviews. Health was conceptualized in a holistic manner, consistent with the view of the World Health Organization and Health Canada. The caregiving experience, as described in this study, was life changing and consuming. Anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
99
2
13

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(121 citation statements)
references
References 14 publications
7
99
2
13
Order By: Relevance
“…This study contributes much needed information about spirituality and caregivers of stroke survivors, which is an outcome of their participation in the e-mail discussion group. This is a distinction between this study and others reported (Jones-Cannon & Davis, 2005;Murray, 2004;Paun, 2004;Pierce, 2001;Sawatzky & Fowler-Kerry, 2003;Taylor, 2003Taylor, , 2006Theis et al, 2003), as messages were most often unsolicited and arose from the caregivers or in response to the nurse specialist facilitator and other caregivers, providing an indication of what was meaningful to them during the first year of caring. Spirituality, which gave caregivers of stroke survivors hope, sustenance, and a chance to express themselves more fully, enabled them to cope during a time of change.…”
contrasting
confidence: 62%
See 1 more Smart Citation
“…This study contributes much needed information about spirituality and caregivers of stroke survivors, which is an outcome of their participation in the e-mail discussion group. This is a distinction between this study and others reported (Jones-Cannon & Davis, 2005;Murray, 2004;Paun, 2004;Pierce, 2001;Sawatzky & Fowler-Kerry, 2003;Taylor, 2003Taylor, , 2006Theis et al, 2003), as messages were most often unsolicited and arose from the caregivers or in response to the nurse specialist facilitator and other caregivers, providing an indication of what was meaningful to them during the first year of caring. Spirituality, which gave caregivers of stroke survivors hope, sustenance, and a chance to express themselves more fully, enabled them to cope during a time of change.…”
contrasting
confidence: 62%
“…Providing an opportunity for the caregiver to openly talk about his or her relationship with a greater power may provide comfort and alleviate stress. Practicing rituals, the second theme, was important to these caregivers and an emphasis on them such as prayer, church attendance, and meditation were also helpful strategies in dealing with their situation (Sawatzky & Fowler-Kerry, 2003). To identify practices or rituals important to caregivers, nurses need to be cognizant of the caregiver's person and surroundings.…”
Section: Discussionmentioning
confidence: 99%
“…S'il existe une forme d'enrichissement à être proche-aidant (Li et Loke, 2013;Yatchmenoff et al, 1998), les recherches insistent davantage sur les tensions engendrées par ce rôle : les proches-aidants présentent de plus hauts niveaux de fatigue, de douleurs musculaires ainsi que de maladies cardiaques et chroniques que les personnes sans responsabilités de soin (Sawatzky et Fowler-Kerry, 2003;Cannuscio et al, 2004;Carretero et al, 2009;Feinberg et al, 2006;Robison et al, 2009;Bialon et Coke, 2012;Williams et al, 2016). Sur le plan émotionnel, ils font face à de plus hauts niveaux de stress, de dépression et de culpabilité que les non-prochesaidants (Duxbury et al, 2009;Rajnovich, Keefe et Fast, 2005;Scharlach, 1994;Smith et Dumas, 1994;Pyper, 2006).…”
Section: Les Couts Des Responsabilites De Soinunclassified
“…À l'intérieur de la population des personnes aidantes, les femmes sont surreprésentées (Ford, Goode, Barrett, Harrell, & Haley, 1997;Lee & Porteous, 2002;Strang, 2001, Szinovacz & Davey, 2008. Ce serait elles, à près de 75 %, qui occuperaient ce rôle dans la société occidentale (Sawatzky & Fowler-Kerry, 2003). Il semble que ce soit également elles qui subissent le plus de contrecoups liés à l'accomplissement de ce rôle (Kramer & Kipnis, 1995, Lutzky & Knight, 1994, Patti et al, 2007.…”
unclassified
“…(da Cruz, Pimenta, Kurita & de Oliveira, 2004). Ce sont les femmes qui sont majoritairement présentes dans le domaine de l'aide et du soutien apportés à des personnes ayant des incapacités (Lee & Porteous, 2002;Sawatzky & Fowler-Kerry, 2003), et celles-ci vivraient plus de détresse psychologique liée à leur rôle que les hommes (Kramer & Kipnis, 1995;Patti et al, 2007).Une dynamique particulière est observée chez les personnes aidantes qui prennent soin de leur partenaire qui lutte avec des incapacités physiques, de la douleur, de la fatigue 21 ou de la tourmente. En effet, la personne atteinte est placée dans une situation de dépendance accrue envers son ou sa conjoint-e qui lui apporte de l'aide (D'Ardenne, 2004).…”
unclassified